(untitled) (Configurazioni. Research on contemporary poetry, 2023)
The paper introduces the proceedings of the fourth edition of the seminar “Apice’s Poets”, In the Eye’s Rhythm. Poetic Iconotexts in the Second Half of the Twentieth Century, held at the University on Milan on October 25th, 2021.